Study of Moisture Ratio Variation During Microwave Drying Process of Avocado Pulp - Nguyen, Duc Trung; Phan, Minh Thuy (Old Journal, 2019)
Microwave drying (MWD) process of avocado (Persea Americana Mills) pulp is surveyed at laboratory scale via the variation of moisture ratio (MR) of drying material (DM) due to time. The value of MR(t) function is in the range from 0 to 1 for every drying technology mode and all kinds of DM. Rotary tray MWD equipment is applied in the experiments with different values of specific power ratio (SPR). Experiment data is regressed by the CFT (Curve Fitting Toolbox) toolbox of Matlab software in order to determine the parameters of the proposed models. The compatibility of regressive models is tested via reduced chi square distribution (χ²).